Efficacy of botulinum toxin in masseter muscle hypertrophy for lower face contouring. (28th February 2022) - Kundu, Nisha; Kothari, Rohit; Shah, Nimish; Sandhu, Sunmeet; Tripathy, Durga Madhab; Galadari, Hassan; Gold, Michael H.; Goldman, Mitchel P.; Kassir, Martin; Schepler, Hadrian; Grabbe, Stephan; Goldust, Mohamad
Abstract: Background: Masseter muscle hypertrophy (MMH) usually presents with cosmetic concerns as it may lead to widening of the lower face. Apart from the traditional surgical approaches, botulinum toxin type A (BTA) injection is a non‐invasive treatment option available. There are no standard guidelines for this procedure. Objectives: To study the efficacy of botulinumtoxin A in MMH for lower face contouring. Methodology: The Cochrane Library, PubMed/MEDLINE, Google‐scholar, Science‐Direct database, and ResearchGate from inception until September 2021 were searched using the keywords "botulinumtoxin type A, " "masseter muscle hypertrophy, " "lower face contouring, " and "masseter botox." All available retrospective and prospective studies, case‐series, case‐reports, and expert reviews were included with an emphasis on efficacy of BTA in MMH and units injected into the muscle, points of placement, adverse events, and the duration of its effect. Reference lists of the resultant articles, as well as relevant reviews, were also searched. Result: 40 articles were shortlisted for the review, of which 14 studies with sample‐size ≥10 in accordance with the study requirements were summarized in a tabular form for analysis and easy comparison and reference. Conclusion: BTA injection is a non‐invasive, safe, and effective treatment for MMH. The optimum number of BTA units could not be ascertained due to wide variability in the studies as well as ethnicity of patients and extent or some measurement of MMH. The points of placement of injection should be well within the boundaries of the masseter muscle. The maximum effect of BTA after a single injection session is usually seen in 3 months, and the duration may last for 6–12 months. Multiple injection sessions may be required to maintain a long‐term effect. Injection technique and total number of injection units of neuromodulator must be individualized for each patient.